2017
DOI: 10.1108/jes-03-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

The lead-lag relationship between US industry-level credit and stock markets

Abstract: Purpose The purpose of this paper is to identify the arbitrage opportunities between US industry-level credit and stock markets with a focus on dynamic lead-lag relationships given that these markets involve heterogeneous agents operating over various time horizons. Design/methodology/approach The authors use daily data of 11 US industries stock markets and their credit counterparts to model the dynamic dependence and casual nexuses using time-frequency approach, namely, wavelet squared coherence (WTC). Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…The literature has mainly focused on the analysis of returns and generally uses corporate US data. Most studies, such as [7][8][9], among others, point to the leadership of stocks over CDSs, which is in line with the results of [10,11] for sovereign CDS data. However, the literature on the relationship in terms of volatility is scarce and provides contradictory results.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The literature has mainly focused on the analysis of returns and generally uses corporate US data. Most studies, such as [7][8][9], among others, point to the leadership of stocks over CDSs, which is in line with the results of [10,11] for sovereign CDS data. However, the literature on the relationship in terms of volatility is scarce and provides contradictory results.…”
Section: Introductionsupporting
confidence: 68%
“…In [8], it is also established that it is equity returns that respond to CDS returns, but not the other way around. In a more recent study [9], it is confirmed that for all US industries, the equity market leads the CDS market, and it is concluded that this causality has a dynamic character and is counter cyclical. Using the same sample, in [21], the determinants of this causality are studied, finding that the volatility of the stock market, the business conditions, the default premiums, the Treasury bond rate, and the slope of the yield curve are the major explanatory factors of this relationship.…”
Section: Literature Reviewmentioning
confidence: 85%
“…Most of these studies used spot and futures returns from commodity markets, although some explored lead-lag relationships between exchange rates (Basnarkov et al, 2020), futures speculation types (i.e. short-run, long-run, and excessive) and price volatility (Algieri and Leccadito, 2019), daily sovereign credit default swap spread changes (Bouri et al, 2019), liquid and illiquid indices (Chaibi, 2014), electricity market spot and futures prices (Da Silva et al, 2019), Eurozone business cycles (Duran and Ferreira-Lopes, 2017), lean hogs and pork bellies (Jackline and Deo, 2011), soybean bases of different regions (Kurfman, 2011), interest rates (McLeod, 2008), leader and follower stocks (Rusmanto et al, 2016;Xia et al, 2018), credit default swaps and stock markets (Shahzad et al, 2017), credit and housing markets (Shen et al, 2016), oil and agricultural markets (Tiwari et al, 2018), volatility and trading volume (Todorova and Clements, 2018), bonds and the underlying stocks (Tolikas, 2018), BRIC countries' stock exchanges (Tonin et al, 2013), and the returns of different metals (Tweneboah and Alagidede, 2018). Most of the studies used daily data, although some data was presented in intervals of seconds, minutes, 5 min, hours, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent research that demonstrates the empirical support that investment horizon among investors matters in credit and stock markets is found in Shahzad, Ferrer, Hammoudeh and Jammazi (2018) and Shahzad, Nor, Sanusi and Kumar (2017), inequity and bond market (Sakemoto, 2018). However, the literature reveals a deficiency.…”
Section: Literature Reviewmentioning
confidence: 99%